2014
DOI: 10.1108/jsm-07-2013-0205
|View full text |Cite
|
Sign up to set email alerts
|

The differentiated effects of CSR actions in the service industry

Abstract: Corporate Social Responsibility (CSR) is becoming a common strategy within medium and large companies, which explains the growing number of studies and disciplines focusing on it. One stream of research examines the effects of CSR on a firm's performance, such as its market value, suggesting that the financial performance outcomes of responsible corporate behavior may vary depending on firm-specific and industry-related factors. This study attempts to explain why the impact of CSR initiatives may be different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
65
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(68 citation statements)
references
References 95 publications
3
65
0
Order By: Relevance
“…There has been a global shift from manufacturing economy to a service economy (Grant & Parker, 2009). Further, CSR activities are more beneficial to service providers than to manufactures (Casado‐Díaz, Nicolau‐Gonzálbez, Ruiz‐Moreno, & Sellers‐Rubio, 2014). Accordingly, this study aims to examine the relationships between perceptions of CSR and internal and external outcomes among service employees.…”
Section: Introductionmentioning
confidence: 99%
“…There has been a global shift from manufacturing economy to a service economy (Grant & Parker, 2009). Further, CSR activities are more beneficial to service providers than to manufactures (Casado‐Díaz, Nicolau‐Gonzálbez, Ruiz‐Moreno, & Sellers‐Rubio, 2014). Accordingly, this study aims to examine the relationships between perceptions of CSR and internal and external outcomes among service employees.…”
Section: Introductionmentioning
confidence: 99%
“…It further contends that CSR improves firm performance by protecting all stakeholders' interests and by decreasing the risk of attaining resources. A B. Casado-Díaz, J L. Nicolau-Gonzálbez, F Ruiz-Moreno and R Sellers-Rubio [95] explored CSR activities and found that CSR has a positive impact on FP. A firm with CSR activities can improve its relationships with stakeholders, ultimately leading to higher profits [96,97].…”
Section: Corporate Social Responsibility and Firm Performancementioning
confidence: 99%
“…In the analysis of this paper, the ICT industry is categorized into two sectors to examine whether the CSP–FP relationship differs between service firms and non‐service firms. For instance, Casado‐Díaz et al () confirm that CSP activities have a more positive effect on market value in service firms than in non‐service firms. They argue that CSP delivers greater and more valuable information to investors and consumers, which reduces informational asymmetries and boosts reputation.…”
Section: Literature Review and Hypothesis Development For The Relatiomentioning
confidence: 99%